2012
DOI: 10.1016/j.molcel.2012.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Processive Steps in the Reverse Direction Require Uncoupling of the Lead Head Lever Arm of Myosin VI

Abstract: SUMMARY Myosin VI is the only known reverse-direction myosin motor. It has an unprecedented means of amplifying movements within the motor involving rearrangements of the converter subdomain at the C-terminus of the motor and an unusual lever arm projecting from the converter. While the average step size of a myosin VI dimer is 30–36nm, the step size is highly variable, presenting a challenge to the lever arm mechanism by which all myosins are thought to move. Herein we present new structures of myosin VI that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 35 publications
(64 reference statements)
3
25
0
Order By: Relevance
“…Following a design principle established in previous work on engineered myosin lever arms 6,7,9,19 , we made use of a helix-sharing junction in which the C-terminal helix of the truncated myosin VI lever arm was fused to the N-terminal helix of the L7Ae domain. Guided by crystal structures of L7Ae-RNA 22 and of myosin VI 23,24 , we aligned the terminal helices and optimized the phasing of the junction to orient a bound kink-turn motif as a structural foundation from which to build extended RNA lever arms. The interaction of L7Ae with kink-turn motifs has been previously exploited in nanotechnology and synthetic biology applications 2527 , and yields stable complexes with reported K d values of ~1 nM and dissociation rates of ~2–7 × 10 −4 s −1 25,27,28 .…”
mentioning
confidence: 99%
“…Following a design principle established in previous work on engineered myosin lever arms 6,7,9,19 , we made use of a helix-sharing junction in which the C-terminal helix of the truncated myosin VI lever arm was fused to the N-terminal helix of the L7Ae domain. Guided by crystal structures of L7Ae-RNA 22 and of myosin VI 23,24 , we aligned the terminal helices and optimized the phasing of the junction to orient a bound kink-turn motif as a structural foundation from which to build extended RNA lever arms. The interaction of L7Ae with kink-turn motifs has been previously exploited in nanotechnology and synthetic biology applications 2527 , and yields stable complexes with reported K d values of ~1 nM and dissociation rates of ~2–7 × 10 −4 s −1 25,27,28 .…”
mentioning
confidence: 99%
“…We suggest that the location of the hinge around which the lever arm rotates is close to residue N785 (located in ins2), at the beginning of a region identified as pliant in the PrePS state (41). Within a few microseconds from the start of the PrePS→R transition N785 binds the converter and then fluctuates around an average position (SI Appendix, Figs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the power stroke of MVI occurs with a two-step mechanism, in which first the converter rotates, and then, once the backward load from the actin-bound trailing head is relieved, the lever arm rotates toward the R-state configuration (41). In this picture, it was argued that at the end of the first step the converter domain is in a PrePS state-like configuration, but it has moved toward the R-state position on the motor domain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations